OPTIMIZATION PARAMETERS OF MICROWAVE SPECTRUM ANALYZER RADIOFREqUENCY AND DIGITAL PATH - V. N. Putilin; S. V. Zdorovtsev; A. V. Melnikov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The paper deals with improving the performance of the RF path and the digital path of microwave multi-function measuring devices into range up to 8 GHz. Development of the two-loop PLL system was performed using a VCO and DDS and allowed us to realize the required parameters of measuring devices. Additionally, the development and research of IQ imbalance correction method of quadrature components of the signal in a digital IF path was carried out, which enabled to reduce the signal distortions and incorporate the requirements for multi-function measuring devices